(untitled) (Emergency Care Journal, 2021)
The pathogenesis of COVID-19 appears to be characterized by a dysregulated immune response. During the first pandemic wave in Lombardy, we started to administer glucocorticoids to some patients with severe respiratory failure requiring support with Continuous Positive Airway Pressure (CPAP) therapy. We retrospectively collected data to identify the effect of glucocorticoids in this COVID-19 particular population. With a multidisciplinary consensus, we administered to selected patients with severe COVID-19 disease (PaO2/FiO2 159±71 mmHg) 0,91 mg/kg/die of methylprednisolone equivalent dose after a median of 8 days of hospitalization. In our study we compared 57 patients from the steroid group with 123 from the control group: the event of invasive mechanical ventilation or death was reduced by 43% between steroid group and control group (19.3 % vs. 34.1 % respectively, p=0.001) and mortality was reduced by about 31% between steroid and usual care alone (15.8 % vs. 22.8 % respectively, p=0.011). Corticosteroids in selected COVID-19 patients may have a relevant impact on outcome, better profiling of the heterogeneity of this disease may be essential to guarantee the best treatment choices.